The Motivation of the KOPTI in South Cikampek Village in Improving the Performance of Its Employees - Agustian, Muhamad Alif; Fadli, Uus (Integrasi Sains Media, 2023)
The purpose of this study is to find out what motivation is used in improving employee performance and also to find out the factors that influence improving employee performance at work. This research uses a descriptive qualitative method: interviews and direct observations of tofu and tempeh producer cooperatives in South Cikampek village. The study results were obtained from interviews with several business owners of tofu and tempeh producers and their employees. Work motivation provided by business owners is very influential in improving employee performance. It can create a good relationship between business owners and employees and build concern for employees in several factors, such as work quality, responsibility, and initiative. With the increase in employee performance, all things related to human resources can be appropriately maximized to achieve job satisfaction through good work quality, quantity, and good relationships to create a good work environment.